Analisis Faktor Minat Petani Dalam Partisipasi Program Makmur PT. Petrokimia Gresik di Kalurahan Kalisoro, Kecamatan Tawangmangu, Kabupaten karanganyar - Irhan Wardana Wahyu Syaputra; Ananti Yekti; Agus Wartapa (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to analyze the factors that influence farmers' interest in participating in the Makmur Program initiated by PT Pupuk Indonesia and implemented by PT Petrokimia Gresik in Kalisoro Village, Tawangmangu District, Karanganyar Regency. This program is an effort to empower farmers through the provision of production facilities, technical assistance, and support for increasing productivity. The research method used is a quantitative approach with binary logistic regression analysis techniques. The number of respondents in this study was 70 farmers, who were taken proportionally from farmer groups that had and had not participated in the program. The results of the analysis show that of the six variables studied age, length of farming, productivity, agronomic role, role of farmer groups, and role of resource providers there are two variables that have a significant effect on farmers' interest in participating in the Makmur Program, namely age and productivity. The age variable has a significant positive relationship, which means that the older the farmer, the greater the tendency to participate in the program. Meanwhile, the productivity variable also shows a positive effect, indicating that farmers with high yields are more open to programs that support their farming efforts. Based on these findings, it can be concluded that the success of participation in the Makmur Program is influenced by internal factors of farmers, especially age and productivity achievement. The results of this study are expected to be the basis for policy makers in designing communication strategies and approaches that are more targeted to farmer groups.